Survei Tingkat Teknik Dasar Servis Bola Voli Pada Siswa Kelas VII SMP Ma'arif Tukdana - Suprapto, Dedi; Yudhi Kharisma; Agi Ginanjar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the profile of basic volleyball service skills among seventh-grade students at Ma'arif Tukdana Junior High School. This study is descriptive in nature with a quantitative approach and uses testing and measurement methods. The participants in this study were 31 male seventh-grade students at Ma'arif Tukdana Junior High School. The instrument used in this study was the volleyball skills test from Russel-Lange. The results of the analysis showed an average score of 24,19 and a standard deviation of 6,42. The results of the volleyball serve test, which was conducted using the volleyball skill test from Russel-Lange, showed that 3 students were in the very good category, 5 students were in the good category, 14 students were in the fair category, 8 students were in the poor category, and 1 student was in the very poor category. The percentage is 10% in the very good category, 16% in the good category, 45% in the fair category, 26% in the poor category and 3% in the very poor category. It can be concluded based on the overall average results of the students that the level of the Volleyball Service Test at SMP Ma'arif Tukdana, Indramayu Regency, in 2025, which had 31 students, using the Russell-Lange volleyball skills test, falls into the adequate category.